Existence and multiplicity results for some superlinear elliptic problems on RN - Bartsch, Thomas; Wang, Zhi-Qiang (Communications in partial differential equations, 1995)
We study the semilinear elliptic PDE in RN The nonlinearity ƒ will be superlinear and subcritical. We prove the existence 0f a positive solution under various hypotheses on b. If and ƒ is odd in u, then we also discuss the dependence of the number of (possibly sign changing) solutions on the parameter λ. We do not assume that b or ƒ have a limit for .
Elektronische Reproduktion der Druck-Ausgabe 08. Mai 2007
Im Titel ist der Buchstabe "N" hochgestellt
Gesehen am 17.05.2023